Chemical dosing device of sewage treatment equipment capable of automatically computing chemical dose via PCL - The inventor has waived the right to be mentioned (2016)
The invention discloses a chemical dosing device of sewage treatment equipment capable of automatically computing the chemical dose via a PCL. The chemical dosing device comprises a raw water inlet pipe, a raw water outlet pipe and a chemical reaction tank hung in the air, wherein a gas pipeline is arranged at the bottom of the chemical reaction tank, passes through the bottom of the chemical reaction tank and is connected with a ball; a plurality of vent holes are uniformly formed in the ball; at least a powdery chemical box is arranged at the top of the chemical reaction tank; a chemical delivery pipe is arranged at the bottom of each powdery chemical box; the other end of the chemical delivery pipe is connected with a sprinkler head; a flow sensor and a flow rate sensor, which are connected with a PLC, are arranged on the raw water inlet pipe. After adopting the structure, the chemical dosing device has the beneficial effects that the chemical reaction tank has small volume, is hung in the air and does not